Optimization Modelling of Parcel Delivery Problem in a Distribution Network - Yee, Kee Man; Mahathir Mohamad (Enhanced Knowledge in Sciences and Technology, 2024)
With the rapid growth in E-commerce in Malaysia as a result of Covid-19, demands for courier services are on the rise. As such, the focus of the study will be placed on route optimization for courier services to enhance the process of parcel deliveries. Particularly in the context of the courier scene in Johor Bahru, Malaysia. The study’s objective is to apply genetic algorithms and dynamic programming in finding the optimal delivery path based on distance and time spent, and to compare their performance. The scope of the study focuses on modeling parcel delivery paths and handling time between hubs using data collected from Google Maps and analysis conducted using Matlab. The significance of the study lies in its potential to improve delivery efficiency, reduce shipment periods, and enhance customer satisfaction in response to the increasing demand for e-commerce platforms in Malaysia.